Editorial: Impact of Covid 19 on Trade, FDI, Real Exchange Rate and Era of Digitalization: Brief Review Global Economy During Pandemic - Handoyo, Rossanto Dwi (Universitas Airlangga, 2020)
The COVID-19 pandemic has not only triggered an unprecedented global health crisis but also a global economic, trade and investment crisis. Global Trade in merchandise fall from 12% to 32% in 2020. FDI flows are projected to fall further by 30% to 40% in 2020-202. The decline in trade is a reflection, instead of a cause, of the economic contraction that occurred, caused by rising trade costs - from disruptions in transportation, logistics and supply chains, as well as trade restrictions. At the same time, the COVID-19 pandemic is driving an overall digital transition in society and industry. Since June 2020, there has been increasing trend in social media and other apps, it rose by 38 percent while streaming video increased to 35 percent. A significant increase was in the use of conference tools during the COVID-19 pandemic and it will have an impact on improving technology infrastructure. Keywords: Pandemic COVID-19, Trade in Merchandise, FDI, Exchange Rate and Digitalization